유수분화기 식생지수와 SPAD값에 의한 벼 질소 수비 시용량 결정 - 김민호; Min Ho Kim; 부금동; Jin Dong Fu; 이변우; Byun Woo Lee (Korean journal of crop science, 2006)
목표 수량과 단백질함량을 얻기 위한 질소 수비처방을 위해서는 유수형성기 전후 생체정보의 정확한 진단뿐만 아니라 유수형성기 이후 작물의 질소 축적 및 이에 따른 수량 및 미립 단백질 함량 반응이 정량화 되어야 한다. 본 연구에서는 유수분화기 생육 및 질소영양상태를 잘 대표하는 RVI green과 현재 널리 이용되고 있는 SPAD값의 유수분화기와 유수분화기 1주일전의 측정치 및 유수분화기부터 수확기까지 즉 생식생장기 지상부 질소 축적량(PNup)을 변수로 하는 수량 및 단백질함량 예측 중회귀 모델과 PNup 예측 회귀모델을 작성하여 이들의 수비 처방에의 이용 가능성을 검토하였다. 1. 유수분화기 및 유수분화기 1주일전의 RVIgreen과 SPAD값, 그리고 PNup을 이용하여 얻은 수량과 단백질함량의 중회귀모형은 어느 경우에나 모델의 결정계수(R2)가 0.9 이상으로 매우 높았다 2. 수량을 최대로 하는 생식생장기 질소흡수량(PNup)은 유수형성기 전후 RVIgreen이 증가할수록 감소하는 경향을 보였는데 본 연구의 유수형성기 전후 RVIgreen 범위로 보면 9~13.5kg/10a 으로 추정되었다. 또한 PNup은 유수형 성기 전후 SPAD값과는 무관하게 10~11kg/10a 범위로 나타났다. 3. 미립의 단백질함량을 7% 이하로 하는 유수형성기 질소흡수량은 유수형성기 전후 RVIgreen과 SPAD값이 증가할수록 감소하는 경향으로 어느 경우에나 6~8kg/10a 로 추정되어 최대수량을 위한 생식생장기 질소흡수량 9~13.5kg/10a 보다 크게 낮았다. 따라서 고품질 쌀 생산을 위한 수비 처방을 위해서는 수량보다도 단백질함량을 기준으로 하여 처방하여야 할 것으로 판단되었다. 4. 본 실험결과 수비질소의 회수율은 53~83% 의 변이를 보였는데, 생식생장기 생육량이 많을 수록 회수율이 증가하는 경향이었으며, 수비 시용량이 증가함에 따라서 감소하였다. 생식생장기 천연질소공급량은 3~4kg/10a 범위였으며 유수분화기 생육량이 많을 경우 증가하는 경향이었다 수비 질소시비량 및 유수분화기 생육 및 질소 영양 지표들을 예측변수로하는 PNup 예측모델을 작성하였으며 이 모델들은 적합도가 매우 높았다. 5. 영양생장기 생육 및 질소영양 상태의 비파괴적 측정치를 이용하여 목표 수량과 단백질함량에 달할 수 있도록 수비질소 시용량을 결정할 수 있을 것으로 판단되었다. 그러나 여기서 제시한 모델들이 광범위한 조건에서 이용될 수 있기 위해서는 보다 다양한 품종, 토양, 기상 조건에서 모델의 검증과 보완이 되어야 할 것으로 판단된다. The core questions for determining nitrogen topdress rate (Npi) at panicle initiation stage (PIS) are 'how much nitrogen accumulation during the reproductive stage (PNup) is required for the target rice yield or protein content depending on the growth and nitrogen nutrition status at PIS?' and 'how can we diagnose the growth and nitrogen nutrition status easily at real time basis?'. To address these questions, two years experiments from 2001 to 2002 were done under various rates of basal, tillering, and panicle nitrogen fertilizer by employing a rice cultivar, Hwaseongbyeo. The response of grain yield and milled-rice protein content was quantified in relation to RVIgreen (green ratio vegetation index) and SPAD reading measured around PIS as indirect estimators for growth and nitrogen nutrition status, the regression models were formulated to predict PNup based on the growth and nitrogen nutrition status and Npi at PIS. Grain yield showed quadratic response to PNup, RVIgreen around PIS, and SPAD reading around PIS. The regression models to predict grain yield had a high determination coefficient of above 0.95. PNup for the maximum grain yield was estimated to be 9 to 13.5 kgN/10a within the range of RVIgreen around PIS of this experiment. decreasing with increasing RVIgreen and also to be 10 to 11 kgN/10a regardless of SPAD readings around PIS. At these PNup's the protein content of milled rice was estimated to rise above 9% that might degrade eating quality seriously Milled-rice protein content showed curve-linear increase with the increase of PNup, RVIgreen around PIS, and SPAD reading around PIS. The regression models to predict protein content had a high determination coefficient of above 0.91. PNup to control the milled-rice protein content below 7% was estimated as 6 to 8 kgN/10a within the range of RVIgreen and SPAD reading of this experiment, showing much lower values than those for the maximum grain yield. The recovery of the Npi applied at PIS ranged from 53 to 83%, increasing with the increased growth amount while decreasing with the increasing Npi. The natural nitrogen supply from PIS to harvest ranged from 2.5 to 4 kg/10a, showing quadratic relationship with the shoot dry weight or shoot nitrogen content at PIS. The regression models to estimate PNup was formulated using Npi and anyone of RVIgreen, shoot dry weight, and shoot nitrogen content at PIS as predictor variables. These models showed good fitness with determination coefficients of 0.86 to 0.95 The prescription method based on the above models predicting grain yield, protein content and PNup and its constraints were discussed.